INTEGRASI FILSAFAT HUMANISTIK DAN TEORI BELAJAR SOSIAL DALAM PENGEMBANGAN MODEL PEMBELAJARAN PERSONAL DI SEKOLAH DASAR - Tiara Wulandari (ADISAM PUBLISHER, 2026)
The aim of this study is to analyze the integration of humanistic learning theory in the practice of differentiated instruction in the 4th grade of SD Negeri 04 Karangsari, Jatiyoso, Karanganyar. This research employs a descriptive qualitative approach with a case study methodology. Data is collected through observation, interviews, and documentation techniques. In data analysis, the researcher will identify patterns and key findings from the interview, observation, and documentation data. Data validation is conducted by ensuring consistency among various data sources and avoiding research bias.